Predictors of a high defibrillation threshold test during routine ICD implantation. Issue 3 (4th May 2018) - Al-Atia, B.; Vandenberk, B.; Vörös, G.; Garweg, C.; Ector, J.; Willems, R.
Abstract: Background: There is growing evidence that routine defibrillation threshold (DFT) testing during implantable cardioverter defibrillator (ICD) implantation is not necessary. However a small group of patients might be at risk if no DFT testing is performed. Methods: Patients with a new pectoral ICD implantation in our hospital between 2006 and 2014 were included in a retrospective registry. A clinical high DFT was defined as a safety margin <10 J of the maximal device output. Logistic regression for prediction of high DFT was performed using patient characteristics, clinical, echocardiographic and device-related parameters. Results: DFT testing was performed in 788/864 (91.2%) procedures. In 76 (8.8%) patients no DFT testing was performed mainly due to atrial fibrillation, intra-cardiac thrombus, hemodynamic instability or logistical reasons. A high DFT was present in 44 (5.6%) patients. A QRS duration ≥150 ms, a low left ventricular ejection fraction (LVEF ≤25%), a severely dilated left ventricle ≥60 mm and right sided pre-pectoral implantations were univariate predictors of a high DFT. Independent predictors of a high DFT were a LVEF ≤25% (HR 2.195, 95%CI 1.085–4.443) and right sided pre-pectoral implantations (HR 3.135, 95% CI 1.186–8.287). Conclusions: A high DFT is still present in about 5% of patients and is more frequent in patients with a severely dilated left ventricle, a very low LVEF, right sided pre-pectoral implantation and wider QRS duration. It might be clinically important to continue DFT testing in these high risk patients.